2011
DOI: 10.3109/09513590.2011.579664
|View full text |Cite
|
Sign up to set email alerts
|

Serum anti-Müllerian hormone, inhibin B, and total inhibin levels in women with hypothalamic amenorrhea and anorexia nervosa

Abstract: The present data showed that neuroendocrine forms of amenorrhea are associated with an impaired inhibin secretion while not AMH. These data indirectly support that AMH is an excellent marker of ovarian reserve and its secretion is not influenced by the hypothalamic-ovarian axis activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 23 publications
3
7
1
Order By: Relevance
“…This same group (24) also reported that women with HH had higher AMH levels and a higher mean ovarian volume compared with controls. These findings are also in discordance with results from a study published by Luisi et al (25)., in which no significant difference in AMH was found between a group of women with hypothalamic amenorrhea and a group of women consisting of healthy controls.…”
Section: Discussioncontrasting
confidence: 85%
“…This same group (24) also reported that women with HH had higher AMH levels and a higher mean ovarian volume compared with controls. These findings are also in discordance with results from a study published by Luisi et al (25)., in which no significant difference in AMH was found between a group of women with hypothalamic amenorrhea and a group of women consisting of healthy controls.…”
Section: Discussioncontrasting
confidence: 85%
“…Previous studies on ovarian function and TM mainly focused on ovarian reserve and generally supported an impairment: AMH and AFC are consistently lower [4,[7], [8], [9], [10], [11]]. Our data is in agreement with these findings since both biomarkers resulted reduced in exposed women.…”
Section: Discussionsupporting
confidence: 92%
“…Recent studies also revealed that patients with TM have lower levels of anti-Mullerian hormone (AMH) and reduced antral follicular count (AFC), suggesting that the peripheral excess of iron may also be toxic locally to the gonads, harming the ovarian reserve [4,[7], [8], [9], [10], [11]]. In addition, iron excess, in particular non-transferrin-bound iron and its redox active form, may actually impact on oocyte quality.…”
Section: Introductionmentioning
confidence: 99%
“…Investigators concluded that both AMH and AFC are accurate predictors of excessive response and both tests appear to have clinical value [3]. Luisi et al [10] more recently showed that secretion of AMH is not influenced by the hypothalamic-ovarian axis activity and is not impaired in hypothalamic amenorrhea. These data also indirectly supports that AMH can also be an excellent marker of ovarian reserve in neuroendocrine forms of amenorrhea [10].…”
Section: Discussionmentioning
confidence: 99%